36=7p=-7(p-5)

Simple and best practice solution for 36=7p=-7(p-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36=7p=-7(p-5) equation:



36=7p=-7(p-5)
We move all terms to the left:
36-(7p)=0
We move all terms containing p to the left, all other terms to the right
-7p=-36
p=-36/-7
p=5+1/7

See similar equations:

| s^2+s=380 | | z/2+7=−50 | | s^2+9s=220 | | 3(2x+1)-3(x+4)=0 | | 0x+2=9x+4 | | (x+17)=(4x-34( | | z=2z-36 | | 24+7x=x−30 | | 0x+2=5x+4 | | 9x-6x+7=1# | | 1/2=a+3/8 | | x+14=22+2x | | 4u=u+93 | | 27x+63=9(3x+7) | | 5(x+2)-3x=2(x | | (2x+48)-(5x-6)=180 | | -4+8x=3(x+7) | | k/8+3=14 | | 13+3x=1+7x | | 1+4x=5x-3 | | (2x+48)=(5x-6) | | 2x+5+3x+3x=25 | | 6(3x-2)=5x+27 | | x^2-0.9x+0.06=0 | | 4x-13.5=50 | | 3x+154=406 | | (2x+7)=(x+23) | | 4x+13.5=50 | | 0.10m=m | | 55x+45x=0 | | 6x-25=5x+1 | | 79+(2x+10)=(6x+1) |

Equations solver categories